Medications use among pregnant women in Ethiopia: A cross sectional study - Mohammed Adem Mohammed, Jemal Hussein Ahmed, Abdulhalik Workicho Bushra, Hisham S. Aljadhey (Journal of Applied Pharmaceutical Science, 2013)
Despite lack of scientific evidence about the safety of some medications, the reported use of medications during pregnancies has increased. This may lead to adverse reproductive outcomes, due to potential risk to the mother and the fetus. In contexts of most developing countries including Ethiopia, it is difficult to elucidate medications use prevalence during pregnancy and their relative contributions to birth defects for several reasons. Institution-based cross sectional study was conducted in Tertiary care hospital Ethiopia. Current medication use data were collected by reviewing patients' charts in the antenatal care follow up clinic, chronic care (internal medicine) as well as psychiatry clinic and by interviewing pregnant women using semi-structured questionnaire. Medications were classified using the United States Food and Drug Administration pregnancy risk classification system. A total of 339 women were included in the study; of which 187 (55.2%) had used at least one prescription and 162(52.2%) had used over the counter medications during pregnancy. The majority of the medications were antibiotics (42.5%) and analgesics (40.1%). 57(16.8%) and 24(7.1%) of medications were prescribed from category D and X respectively. Out of 187 (55.2%) prescription medications used, 51 (15.0%) were obtained without prescribers order. Majority (70.8%) of the women did not have awareness regarding risks associated with self medication. Prescription medications use was 0.08 times less among women with a co-morbidities (AOR 0.08(.05, 0.13), p=0.001) and 2.5 times higher among women from rural areas (AOR 2.53 (1.15, 5.56); P=0.02). Compared to employed women, over the counter medications use were 1.9 times more among house wife women (AOR1.87 (1.12, 3.09), p= 0.02) and about thrice higher among merchant women (AOR 2.88(1.10, 7.55), p= 0.03). Likewise, presence of medical problems was found to have 60% protective against OTC medications use (AOR 0.40 (.26, 0.64), p=0.01). The overall medications use during pregnancy was found to be high. Medications use without prescribers order was common and potentially harmful medications (category-D and X) use appeared to be higher in all trimesters. The findings of this study argue in favor of prescribing some potentially harmful medications which could have been avoided during pregnancy. Majority of the women lacked awareness about the potential risks associated with medications use in pregnancy without prescribers order.
Keywords: Prescription medications, over the counter medicatio